The prefrontal dysfunction in individuals with Internet gaming disorder: a meta-analysis of functional magnetic resonance imaging studies - Meng, Yajing; Deng, Wei; Wang, Huiyao; Guo, Wanjun; Li, Tao (Addiction biology, 2015)
With the advancement in high‐resolution magnetic resonance imaging (MRI) technology and automated analysis, studies on functional MRI (fMRI) made it possible to identify the functional activity of brain in vivo in individuals with Internet gaming disorder (IGD), and to explore the underpinning neuroscience basis of IGD. Yet, no available literature has systemically reviewed the fMRI studies of IGD using meta‐analyses. This study reviewed 61 candidate articles and finally selected 10 qualified voxel‐wise whole‐brain analysis studies for performing a comprehensive series of meta‐analyses employing effect size signed differential mapping approach. Compared with healthy controls, subjects with IGD showed a significant activation in the bilateral medial frontal gyrus (MFG) and the left cingulate gyrus, as well as the left medial temporal gyrus and fusiform gyrus. Furthermore, the on‐line time of IGD subjects was positively correlated with activations in the left MFG and the right cingulated gyrus. These findings implicate the important role of dysfunctional prefrontal lobe in the neuropathological mechanism of IGD. Considering the overlapped role of prefrontal lobe in the reward and self‐regulatory system, our results provided supportive evidence for the reclassification of IGD as a behavioural addiction.